Ancillary tests for brain death - Duvuru, Shyam; Sanker, Vivek; Mishra, Rajeeb Kumar; Sharma, Arvind K.; Lim, Shir Lynn; Baskar, Nisha; Sharma, Vijay K. (Frontiers in Neurology, 2025)
BackgroundAncillary tests are often used in the determination of death by neurologic criteria (DNC), especially when the clinical examination is inconclusive. DNC is widely accepted, as defined by the comprehensive report of the World Brain Death Project. However, there are several medical, legal, religious, ethical, and social controversies. Accordingly, “premature” and “delayed” diagnoses of brain death attract these issues.MethodsDepending upon the availability and experience of the managing medical teams, various ancillary tests are employed for an early and supplementary diagnosis of brain death.ResultsWe describe the practicality, test performance, and utility of some of the commonly employed ancillary tests for the diagnosis of brain death in clinical practice, along with their case examples.ConclusionBrain death is a clinical diagnosis determined by history, physical examination, and adherence to recommended criteria. All ancillary investigations are used as supplementary tests with variable accuracy parameters. These ancillary tests often facilitate an early and “timely” diagnosis of brain death.